Pengaruh Pemberian Bokashi terhadap Efisiensi Dosis Pupuk Npk dan Produktivitas Jeruk Siam (Citrus Nobilis) - Muhajir, Yusuf; Juhan, Muhammad (Program Studi Agroteknologi, 2022)
Siamese citrus productivity is largely determined by the application of fertilizers, both organic and inorganic fertilizers. In mature plants that have passed the phase of maximum vegetative growth velocity (age > 5 years), the fertilizer dose can be approximated by calculating the fruit yield. According to Sutopo (2009). This research is an experimental study on Jeruk Siam Jember land owned by farmers in Rowo Tengah Village, Sumberbaru District, Jember Regency, East Java with an area of ​​​​approximately 2000 M2. The research was conducted from November 2, 2018 to March 20, 2019. The experimental design used a Randomized Block Design with three replications. The treatments studied were:• P0 = plants without fertilizer• P1 = plants fertilized with 30 kg of compost (2 buckets with a volume of 15 liters) (1 sack with a volume of 50 kg of urea);• P2 = plants fertilized with compost as much as 30 kg + 20% dose;• P3 = plants fertilized with compost as much as 30 kg + 40% dose;• P4 = plants fertilized with compost as much as 30 kg + 60% dose.• P5 = plants fertilized with compost as much as 30 kg + 80% dose.• P6 = plants fertilized with compost as much as 30 kg + 100% dose.• P7 = plants only fertilized with 100 % chemical dose.The dosage of chemical fertilizers used refers to the recommendations of Balitjestro (2009). Based on the results of the study, observing the research parameters and calculating the data from the F analysis test and BNT follow-up test, it was shown that the results of treatment 5, namely the administration of bokashi and 80% of the dose of synthetic chemical NPK fertilization, were efficient.